Financial Development, Investment and Economic Growth: Evidence from Nigeria - Ndako, Umar Bida (Journal of Reviews on Global Economics, 2017)
The paper evaluates the relationship among financial development, investment and economic growth in Nigeria. It also examines the role of investment in financial development and how it influences economic growth in Nigeria. The paper applies the standard Vector autoregression (VAR) framework of Johansen, the Inoue (1999) cointegration framework with endogenous structural break model and Johansen et al. (2000) cointegration test with exogenous structural breaks, respectively. After accounting for structural breaks in the series, the study establishes a long-run relationship among financial development, investment and economic growth. This indicates that failure to account for structural breaks in the series may lead to bias estimates and may mislead policy conclusion. It further reveals that investment is a critical channel that influences economic growth through financial development.